Skin biology - Plotczyk,M; Higgins,C (Woodhead Publishing, 2019)
With a strong focus on materials, engineering, and application, this book is a valuable resource for materials scientists, skin biologists, and bioengineers with an interest in tissue engineering, regeneration, and repair of skin.